2019
DOI: 10.18494/sam.2019.2300
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution Characteristics of Species Diversity Using Geographically Weighted Regression Model

Abstract: The objective of this study is to evaluate the spatial distribution patterns of species diversity at different spatial scales, focusing on the Baekdudaegan Protected Area, which is a biodiversity hotspot in the Republic of Korea. The tree species diversity index (Shannon-Weaver index; H′) was calculated using tree species data from a 1:5k forest-type map, and the spatial analysis was performed with a 1 × 1 km 2 grid. Ten factors were selected to estimate the impact of topographic (elevation, slope, northern sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In recent years, many statistical techniques have been developed to probe into spatial variations in the relationships between spatial variables in the fields of geo-statistics and spatial modeling [32,33]. Geographically weighted regression (GWR), as one of the most powerful geoinformatics-based tools for exploring spatial heterogeneity, has been more widely used in geography, ecology, forestry, and other disciplines [34,35]. GWR is an extension of the traditional regression analysis method for local rather than global parameter estimation, which takes the spatial structure of the data into account in the model, so that the regression coefficients become a function of the geographic location of the observation points, then solves this spatial non-smoothness problem [36].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many statistical techniques have been developed to probe into spatial variations in the relationships between spatial variables in the fields of geo-statistics and spatial modeling [32,33]. Geographically weighted regression (GWR), as one of the most powerful geoinformatics-based tools for exploring spatial heterogeneity, has been more widely used in geography, ecology, forestry, and other disciplines [34,35]. GWR is an extension of the traditional regression analysis method for local rather than global parameter estimation, which takes the spatial structure of the data into account in the model, so that the regression coefficients become a function of the geographic location of the observation points, then solves this spatial non-smoothness problem [36].…”
Section: Introductionmentioning
confidence: 99%
“…species in the desert on a small scale, such as within the scale of 100 m, where topographic factors significantly affect species distribution. Existing studies have shown that geographic and topographic predictors can improved the fitting performance of SDMs substantially 36 .…”
Section: Introductionmentioning
confidence: 99%
“…species in the desert on a small scale, such as within the scale of 100 m, where topographic factors significantly affect species distribution. Existing studies have shown that geographic and topographic predictors can substantially improve the fitting performance of SDMs 37 .…”
Section: Introductionmentioning
confidence: 99%